Bahasa Slang Generasi Milenial sebagai Produk Kreativitas Linguistik pada Media Sosial Instagram - Mulyaningtyas, Rahmawati (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
The millennial generation is a generation that is always side by side with technology. The existence of the millennial generation in social media has given birth to creative linguistic products in the form of slang. This study aims to describe (1) the use of slang on Instagram social media, (2) the development of slang language on Instagram social media, (3) the form of millennial generation creative linguistic products on Instagram social media. The research method used is descriptive qualitative. The data sources used are primary sources in the form of posts and comments from the millennial generation on Instagram social media and secondary data sources in the form of supporting literature. The data collection uses documentation techniques. This study uses descriptive data analysis techniques through four stages of analysis, namely data reduction, data presentation, conclusion drawing, and data verification. The results of this study indicate that slang is often used by the millennial generation in communicating on their social media. Slang has also continued to develop since the 1980's until now. Creative linguistic forms of millennial generation slang include normal words, reduction words, guardian words, abbreviations, and acronyms.